Comparison of monotherapy and combination therapy for older patients with advanced biliary tract cancer: a retrospective study - Ritsuko Oishi; Satoshi Kobayashi; Shuhei Nagashima; Taito Fukushima; Shun Tezuka; Manabu Morimoto; Makoto Ueno; Shin Maeda (BMC Cancer)
Abstract Background The current standard first-line treatment for patients with advanced biliary tract cancer (BTC) is a combination chemotherapy regimen. However, whether the efficacy of combination therapy is superior to that of monotherapy in older patients with BTC remains unclear. Therefore, in this study, we aimed to compare the efficacy and safety of monotherapy with those of combination therapy in such patients. Methods We retrospectively enrolled 157 patients with unresectable or recurrent BTC aged ≥ 75 years who received systemic chemotherapy between August 2011 and November 2020. We compared the efficacy and safety of combination therapy (gemcitabine [GEM] + cisplatin and GEM + S-1) with those of monotherapy (GEM or S-1 alone). We assessed patients’ characteristics, survival, adverse events, and dose intensity. Statistical significance was set at p < 0.05. Results Patients who received monotherapy were older and had worse performance status (PS), lower albumin levels, and higher carcinoembryonic antigen (CEA) levels than those who received combination therapy. The median overall survival (OS) was 16.4 and 12.8 months in the combination therapy and monotherapy groups, respectively (Hazard ratio [HR], 0.69; 95% confidence interval [CI], 0.47–1.01), with a trend towards longer OS observed with combination therapy. However, multivariable analysis did not show superior OS with combination therapy (HR, 1.05; 95% CI, 0.66–1.68). Multivariable analysis also revealed gallbladder cancer, CEA, neutrophil-to-lymphocyte ratio (NLR), and C-reactive protein (CRP) levels as prognostic factors for OS. Regarding safety, the incidence of grade ≥ 3 adverse events was significantly higher in the combination therapy group than in the monotherapy group (79% vs. 53%, p = 0.001); however, the rate of treatment discontinuation was approximately 10% in both groups, with no treatment-related deaths, suggesting that toxicities are manageable even in older patients. Conclusions Combination therapy is not necessarily recommended for older patients with BTC. Selecting an appropriate chemotherapy regimen based on an individual’s condition is important.